DETERMINATION OF HYGROEXPANSION COEFFICIENTS OF WOOD USING ANALYTICAL AND NUMERICAL HOMOGENIZATION - Lucie Kucíková; Michal Šejnoha; Jan Vorel (Acta Polytechnica CTU Proceedings)
This paper is concerned with the determination of hygroexpansion coefficients of wood. Wood is a naturally hygroscopic material, attracting moisture from its surroundings. Its dimensions change depending on the actual moisture content. This dependence is characterized by the coefficient of hygroexpansion. For complex microstructures, this coefficient can be determined, similarly to the coefficient of thermal expansion, either from analytical or numerical homogenization. The homogenization procedure, used in this paper, comprises several steps corresponding to the wood structural composition. Accuracy of this approach is governed by correctness of the chosen input parameters. One of the most important parameters are the volume fractions of the earlywood and latewood. Ascertained dependence of the earlywood and latewood volume fractions on dry wood density is also presented.